Effectiveness of natural species Coagulation as assistants for clarification of turbid water in times of flood in villages and towns of Huaraz and Callejon de Huaylas - Dávila Paredes, Cesar Manuel (2019)
The populations that consume water from water sources must guarantee a good qualityfor their consumption, for that reason the objective was to evaluate the effectivenessof natural species as coagulation aids for the clarification of turbid waters that aregenerated in times of floods in the LLullan rivers, Paria and Chucchun. The appliedmethodology: Collection of coagulants, jar test and determination of optimal dosesand pH. Natural coagulants such as mashua, potato, tara, penca and wheat were used,which were added to the sample in the jar test, obtaining a dose of 45 mg/l at awater pH of 7,5 with concentrations of 5,3%, obtaining important removal values forturbidity parameters and total dissolved solids. When evaluating the efficiency, it wasverified that there is removal of turbidity below the norm, with efficiency values of89,9% for mashua, potato, tara, penca and wheat coagulants, the coagulants reachedthe removal of dissolved solids up to 89% in the tare and a minimum of 13,5% in thewheat value required by the standard. Therefore, it is possible to use natural inputsas coagulants for the clarification of surface waters during rainy seasons and to makethem drinkable and suitable for human consumption